Influencia de la motivacion personal de los socios en la organización del circulo del adulto mayor - san pedro de lloc 2013 - Ventura Grados, Milagros Llanira (2014)
My research has focused on analyze the Influence of personal motivation of the partners of the “Círculo del Adulto Mayor” Organization – CAM from San Pedro de Lloc, 2013, understood in specific form such as intrinsic personal motivation. The research method is descriptive which has a central feature which is the data extraction directly from the source. For this, 25 participants was selected from this Organization, who were administered a structures survey, the answers were corrected and processed related with the variable intrinsic motivation. As a final contribution of research, presents recommendations aimed to reinforce the personal motivation from elderly people to intrinsic level that influence positively on the organization and development of activities contributing to the strengthening from “Círculo del Adulto Mayor”, CAM from San Pedro de Lloc, that will enhance the quality of services and benefit purposeful actions of Older Adults in access to their rights.